Produk Wisata di Grand Watu Dodol Banyuwangi - Kanom, Kanom; Pradiningtyas, Iluh Novi; Rofiq, Cintia; Fintari, Mareta Dwi Putri (Jurnal Ilmiah Pariwisata, 2024)
Grand Watu Dodol one of the most popular tourist attractions in Banyuwangi. The aim research is to find out the tourism products. Research approach is descriptive qualitative with data collection methods using observation, documentation and interviews as well as data analysis techniques using descriptive analysis. The research found are that there is natural potential consisting of various types of coral reefs and the biota that live around them. The condition of Watudodol beach's coral reefs, based on preliminary studies, is still quite good. Apart from that, other biota that live in coral reefs include hawksbill turtles, starfish, ornamental coral fish and sea fans. Condition main attraction domestic and foreign maritime tourists. Information on the types of coral reefs, turtles, fish and other biota that live around coral reefs is very important local tour guides from Grand Watudodol in order to provide understanding tourists who come to Grand Watudodol. Apart from coral reef tourism, there are also snorkeling tours. Snorkeling is a water recreation activity that involves diving on the surface of the water using snorkel equipment. This tourism product has attracted the attention of tourists, especially Banyuwangi, and is able to become one of the tourist development cities in Indonesia. Keywords: tourism, Grand Watu Dodol, Banyuwangi